Ischemic time is a better predictor than door‐to‐balloon time for mortality and infarct size in ST‐elevation myocardial infarction. Issue 7 (2nd September 2015) - Solhpour, Amirreza; Chang, Kay‐Won; Arain, Salman A.; Balan, Prakash; Loghin, Catalin; McCarthy, James J.; Vernon Anderson, H.; Smalling, Richard W.
Abstract : Background: Current guidelines for ST‐elevation myocardial infarction (STEMI) recommend early revascularization with optimal ischemic time (IT) < 120 min and door‐to‐balloon (D2B) time < 90 min. The focus of most studies has been D2B time, while IT is not frequently reported. We tested the hypothesis that total IT is a better predictor than D2B time for mortality and infarct size. Methods and Results: Between December 2008 and April 2013, 786 patients with STEMI were treated in our STEMI center, and 262 of these had cardiac magnetic resonance imaging 3–5 days after the index event. Total IT was defined as time from symptom onset to device activation, while D2B time was defined as hospital arrival to device activation. Patients were divided into three groups according to IT (<120, 120–239, ≥240 min) and into four groups according to D2B time (<30, 30–59, 60–89, ≥90 min). Baseline demographics including age, cardiac risk factors, and LAD infarct location were similar between groups. The 30‐day mortality rate significantly increased across IT groups but did not correlate with D2B time groups. Similarly, infarct size significantly increased across IT groups but did not correlate with D2B time groups. Conclusions: In STEMI patients, IT was a better predictor than D2B time for 30‐day mortality and infarct size. Our findings suggest that the focus of STEMI care should be directed at early initiation of therapy and minimizing IT rather than on D2B time alone. The potential impact of IT reporting in current STEMI registries merits further consideration. © 2015 Wiley Periodicals, Inc.